Faith, burden, and hope in an Indonesian nursing home: An interpretive qualitative study - Tita Hariyanti; Widodo Mardi Santoso; Daniar Dhesilva (Journal of Korean Gerontological Nursing, 2026)
Purpose: This study aimed to explore the perspectives of older adults, caregivers, and managerial informants regarding institutional elder care in Indonesia. Methods: This study used an interpretive qualitative design to explore participants’ lived experiences in a faith-oriented nursing home in Gresik, Indonesia. Fifteen participants, including six older adult residents, six caregivers, and three managerial informants, participated in in-depth semi-structured interviews and non-participant observations. Data were analyzed using thematic analysis guided by interpretive principles, and reporting followed the Consolidated Criteria for Reporting Qualitative Research (COREQ). Ethical approval was obtained from an authorized review board prior to data collection. Results: Five themes identified were (1) family deception and prejudice leading to loss of belonging; (2) praying and working as strategies for emotional endurance; (3) waiting for family with persistent hope amid sorrow; (4) caregivers’ moral and economic tensions in care practices; and (5) systemic scarcity and managerial constraints in institutional elder care. Conclusion: Aging in Indonesian institutional settings reflects complex interactions among cultural expectations, spiritual coping, economic limitations, and structural care challenges. These findings reveal the need for culturally and spiritually grounded models of gerontological care in Indonesian societies.